Macroeconomics for today ( Alternate edition ) - Tucker, Irvin B. (Thomson Learrning, 2005)
This accessible textbook applies the basic principles of economic analysis to the U.S. market, describes tools for measuring an economy's performance, and discusses the federal government's taxing and spending policies, monetary policy, and free trade agreements. The fourth edition adds an appendix on the self-correcting aggregate demand and supply model.